Modeling the Contribution of Gas Hydrate to Corrosion Rate Along the Subsea Pipelines - Obanijesu, Emmanuel; Pareek, Vishnu; Tade, Moses (Taylor & Francis Group, 2014)
This study developed a corrosion predictive model along the deepwater gas pipelines with hydrate as the corroding agent. The model was developed and simulated with primary focus on the thermodynamic properties of each component of the gas mixture and a solution algorithm written with Matlab 6.5 (The MathWorks, Natick, MA) code. The model was validated by comparing the generated results with the outputs of already established laboratory and mathematical corrosion studies; the trends of the results obtained comparatively agreed with these studies to confirm its reliability. The model correctly predicted the relationships between corrosion rate and other thermodynamic parameters such as temperature, pressure, wall shear stress, velocity loss, and pH. This study showed that hydrates can initiate galvanic corrosion, stress cracking corrosion, and erosion-corrosion amongst others. Furthermore, the resulting corrosion rate from the hydrates could be as high as 174 mm/year (0.48 mm/day). This is extremely alarming compared to the industry’s aim to operate below 2 mm/year. At this rate, an underwater pipeline would be subjected to full bore rupture within some days if corrective measures are not quickly taken;hence, the need for further studies.